An Anthropomorphic Analysis of Iwan Fals’ Tikus- Tikus Kantor and Pink Floyd’s Dogs - Box, Kiernan (Journal of Urban Society's Arts, 2024)
Animal-based imagery, including anthropomorphism and zoomorphism, has been a common literary device since ancient times. Contemporary writers of popular song, such as The Beatles, have been particularly frequent exponents of animal-based imagery. This imagery has several uses: it enables subtle or oblique representations of challenging or controversial issues, as well as creating potent, often surreal, imagery which enhances the lyrical quality of the song. Anthropomorphism may take several different forms: comparison (in which animals are compared to humans in instinct and behaviour), cognition (in which animals express human-like thoughts or language), and material conduct (in which animals engage in humanoid actions, including the use of human accessories and technologies). Iwan Fals is a Javanese singer/songwriter renowned for writing songs that address socio-political issues in Indonesia, including topics such as corruption and inequality. Pink Floyd were an English rock band whose songs often explored similar socio-political issues. Both artists have used animal-based imagery in their socio-political songs. Fals’ Tikus-Tikus Kantor may be described as anthropomorphic, whilst Pink Floyd’s Dogs may be interpreted as zoomorphic. Citraan berbasis hewan, termasuk antropomorfisme dan zoomorfisme, telah menjadi perangkat sastra umum sejak zaman kuno. Penulis lagu populer kontemporer, seperti The Beatles, telah menjadi eksponen citraan berbasis hewan yang sangat sering. Citraan ini memiliki beberapa kegunaan: memungkinkan representasi halus atau tidak langsung dari isu-isu yang menantang atau kontroversial, serta menciptakan citraan yang kuat, sering kali surealis, yang meningkatkan kualitas lirik lagu. Antropomorfisme dapat mengambil beberapa bentuk yang berbeda: perbandingan (di mana hewan dibandingkan dengan manusia dalam naluri dan perilaku), kognisi (di mana hewan mengekspresikan pikiran atau bahasa seperti manusia), dan perilaku material (di mana hewan terlibat dalam tindakan humanoid, termasuk penggunaan aksesori dan teknologi manusia). Iwan Fals adalah penyanyi/penulis lagu Jawa yang terkenal karena menulis lagu- lagu yang membahas isu-isu sosial-politik di Indonesia, termasuk topik-topik seperti korupsi dan ketidaksetaraan. Pink Floyd adalah band rock Inggris yang lagu-lagunya sering mengeksplorasi isu-isu sosial-politik yang serupa. Kedua artis tersebut telah menggunakan citraan berbasis hewan dalam lagu-lagu sosial-politik mereka. Tikus- Tikus Kantor karya Fals dapat dideskripsikan sebagai antropomorfik, sedangkan Dogs karya Pink Floyd dapat diinterpretasikan sebagai zoomorfik.